Identifying Barriers to Trainees Addressing Corporal Punishment and Effective Discipline Using Simulation and Semistructured Debriefing. Issue 7 (10th July 2022) - Slingsby, Brett; Moore, Jessica; Wing, Robyn; Garro, Aris; Brown, Linda
Abstract : Objective: The objective of the current study was to examine (1) physician trainee interventions when confronted with a situation in which corporal punishment (CP) occurs in a simulated medical setting and (2) their knowledge, comfort, and experiences shared during a semistructured debriefing. Methods: Themes were developed from simulation sessions from 2018 to 2019, where a convenience sample of training physicians was invited to participate. The simulation involved a medical visit where a caregiver becomes increasingly aggravated, eventually striking her child on the back of the head. There were a total of 7 simulations with one trainee participating while others observed. All trainees subsequently participated in a debriefing and educational session. Results: A total of 37 physician trainees participated. Themes of not having the wording to address CP, not knowing the distinction between CP and physical abuse, previous negative experiences discussing discipline with families, and fear of offending families negatively impacted trainees' ability to intervene during the simulation. Trainees were interested in future education including simulated medical encounters to improve their responses to CP in the future. Conclusions: Trainees felt uncomfortable with intervening when CP was observed and did not know how to provide appropriate guidance to families on discipline. Moreover, performance during the simulation and discussions during the debriefings revealed knowledge gaps regarding the difference between CP and physical abuse, how to word recommendations about CP to caregivers, and what resources should be provided. These data suggest the need for education on CP and discipline to be integrated into pediatric training.